The Benefits of Mediterranean Diet in Systemic Lupus Erythematosus: A Literatur Review - Manuaba, Ida Ayu Ratih Wulansari (Babali Nursing Research, 2024)
Introduction: Dietary patterns have been studied for their influence on the burden of disease in patients with SLE. The Mediterranean diet has been shown to be beneficial in lowering chronic inflammation, but no study has summarized its effect on SLE. This article aims to review the association between the Mediterranean diet and SLE. Methods: A literature review was conducted following PRISMA guidelines. PubMed, ScienceDirect and Google Scholar databases were searched using the keywords Mediterranean diet and SLE. Articles published in English between 2013 and 2023 were included. The initial search yielded 526 records, which were narrowed down to five studies for final inclusion. A narrative synthesis approach was used to analyze the impact of the Mediterranean diet on SLE disease activity. Results: Five cross-sectional studies were included, with a total of 1,165 participants. The studies used the SLE Disease Activity Index (SLEDAI) and the Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SDI) as outcome measurements. Three of the five studies found that higher adherence to the Mediterranean diet was associated with a lower burden of SLE, as measured by reduced SLEDAI and SDI scores. One study found no association between adherence to the Mediterranean diet and SLEDAI or SDI scores, while another study found no association between adherence and the risk of developing SLE. Conclusion: High adherence to a Mediterranean diet may help reduce the damage caused by SLE. Further cohort studies or clinical trials are needed to investigate the impact of diet on SLE.